Exploring the Association of Deliberate Self-Harm With Emotional Relief Using a Novel Implicit Association Test - Gratz, Kim L. (Personal Disord, 2015)
Despite the growing consensus that negative reinforcement in the form of emotional relief plays a key role in the maintenance of deliberate self-harm (DSH), most of the research in this area has relied exclusively on self-report measures of the perceived motives for and emotional consequences of DSH. Thus, the primary aim of this study was to extend extant research on the role of emotional relief in DSH by examining the strength of the association of DSH with emotional relief using a novel version of the Implicit Association Test (IAT). The strength of the DSH-relief association among both participants with (vs. without) DSH and self-harming participants with (vs. without) BPD, as well as its associations with relevant clinical constructs (including DSH characteristics, self-reported motives for DSH, BPD pathology, and emotion dysregulation and avoidance) were examined in a community sample of young adults (113 with recent recurrent DSH; 135 without DSH). As hypothesized, results revealed stronger associations between DSH and relief among participants with versus without DSH, as well as among DSH participants with versus without BPD. Moreover, the strength of the DSH-relief association was positively associated with DSH frequency and versatility (both lifetime and at 6-month follow-up), BPD pathology, emotion dysregulation, experiential avoidance, and self-reported emotion relief motives for DSH. Findings provide support for theories emphasizing the role of emotional relief in DSH (particularly among individuals with BPD), as well as the construct validity, predictive utility, and incremental validity (relative to self-reported emotion relief motives) of this IAT.